Quantum-mechanical predictions of DNA and RNA ionization by energetic proton beams - Galassi, Mariel Elisa (2012)
Among the numerous constituents of eukaryotic cells, the DNA macromolecule is considered as the most important critical target for radiation-induced damages. However, up to now ion-induced collisions on DNA components remain scarcely approached and theoretical support is still lacking for describing the main ionizing  processes. In this context, we here report a theoretical description of the proton-induced ionization of the DNA and RNA bases as well as the sugar-phosphate backbone. Two different quantum-mechanical models are proposed: the first one based on a continuum distorted wave?eikonal initial state treatment and the second perturbative one developed within the fist Born approximation with correct boundary conditions (CB1). Besides, the molecular structure information of the biological targets studied here was determined by ab initio calculations with the Gaussian 09 software at the restricted Hartree?Fock level of theory with geometry optimization.Doubly, singly differential and total ionization cross sections also provided by the two models were compared for a large range of incident and ejection energies and a very good agreement was observed for all the configurations investigated. Finally, in comparison with the rare experiment, we have noted a large underestimation of the total ionization cross sections of uracil impacted by 80 keV protons, whereas a very good agreement was shown with the recently reported ionization cross sections for protons on adenine, at both the differential and the total scale.